MoO3-containing protonated nitrogen doped carbon as a bifunctional catalyst for one-step synthesis of 2,5-diformylfuran from fructose - Zhao, Jun (2020)
A series of protonated molybdenum trioxide and nitrogen-doped carbon (Mo-HNC) were prepared through a facile method and applied as a bifunctional catalyst for the direct synthesis of 2,5-diformylfuran (DFF) from fructose. The molybdenum trioxide loading amount is a key factor either for the synthesis of the catalyst or for the catalytic performance in fructose to DFF transformation. Higher MoO3 loading contributes to higher surface area, and the higher surface area will in turn promote the protonation process, resulting in higher acid density for the catalysts. The catalysts showed good activity in both the dehydration of fructose to HMF and the aerobic oxidation of 5-hydroxymethylfurfural (HMF) to DFF. Under optimized reaction conditions, DFF yield of 77% could be achieved in 9 h at 150 °C. In addition, the Mo-HNC catalyst can be easily separated from the reaction solution and reused without significant loss in activity. Thus, this research provided an efficient method for the transformation of fructose to DFF in tandem reactions of dehydration and oxidation.